Noise and neurotoxic chemical exposure relationship to workplace traumatic injuries: A review. (February 2017) - Estill, Cheryl Fairfield; Rice, Carol H.; Morata, Thais; Bhattacharya, Amit
Abstract: Introduction: More than 5, 000 fatalities and eight million injuries occurred in the workplace in 2007 at a cost of 6 billion and 186 billion, respectively. Neurotoxic chemicals are known to affect central nervous system functions among workers, which include balance and hearing disorders. However, it is not known if there is an association between exposure to noise and solvents and acute injuries. Method : A thorough review was conducted of the literature on the relationship between noise or solvent exposures and hearing loss with various health outcomes. Results : The search resulted in 41 studies. Health outcomes included: hearing loss, workplace injuries, absence from work due to sickness, fatalities, hospital admissions due to workplace accidents, traffic accidents, hypertension, balance, slip, trips, or falls, cognitive measures, or disability retirement. Important covariates in these studies were age of employee, type of industry or occupation, or length of employment. Discussion : Most authors that evaluated noise exposure concluded that higher exposure to noise resulted in more of the chosen health effect but the relationship is not well understood. Studies that evaluated hearing loss found that hearing loss was related to occupational injury, disability retirement, or traffic accidents. Studies that assessed both noise exposure and hearing loss as risk factors for occupational injuries reported that hearing loss was related to occupational injuries as much or more than noise exposure. Evidence suggests that solvent exposure is likely to be related to accidents or other health consequences such balance disorders. Conclusions : Many authors reported that noise exposures and hearing loss, respectively, are likely to be related to occupational accidents. Practical applications : The potential significance of the study is that findings could be used by managers to reduce injuries and the costs associated with those injures. Highlights: 14 studies showed an increase in injuries (or other health outcome) with increased levels of noise exposure. Eight of the nine studies showed significant differences in the health outcome with greater levels of hearing loss. Few studies report a relationship between solvent exposures and injuries. Very few studies report a combined relationship of noise and solvent exposures and injuries.